Ginsenoside Rg1 Ameliorates Cigarette Smoke-Induced Airway Fibrosis by Suppressing the TGF-β1/Smad Pathway In Vivo and In Vitro. (21st March 2017) - Guan, Sibin; Liu, Qian; Han, Fengfeng; Gu, Wen; Song, Lin; Zhang, Yue; Guo, Xuejun; Xu, Weiguo
Abstract : Small airway fibrosis is a key pathological process accompanying chronic obstructive pulmonary disease (COPD) and includes fibroblast/myofibroblast transdifferentiation and excessive extracellular matrix deposition. Ginsenoside Rg1, one of the main active ingredients of Panax ginseng, has been shown to exert an antifibrotic effect in many tissues. However, little is known about the underlying mechanism and whether ginsenoside Rg1 can exert an effect on small airway fibrosis. We investigated the anti-small airway fibrosis effects of ginsenoside Rg1 in human embryonic lung fibroblasts and in COPD rats. We found that ginsenoside Rg1 effectively reduced the degree of pulmonary fibrosis, decreased the expression of α -smooth muscle actin, collagen I, and matrix metalloproteinase 9, and maintained the ratio of matrix metalloproteinase 9 to tissue inhibitor of metalloproteinase 1. Importantly, ginsenoside Rg1 significantly attenuated cigarette smoke extract-induced upregulation of transforming growth factor β 1, TGF- β receptor I, phospho-Smad2, and phospho-Smad3. In addition, ginsenoside Rg1 mimicked the effect of SB525334, a TGF- β receptor I-Smad2/3 inhibitor. Collectively, these results suggest that ginsenoside Rg1 may suppress cigarette smoke-induced airway fibrosis in pulmonary fibroblasts and COPD rats by inhibiting the TGF- β 1/Smad signaling pathway.